Chronic coronary occlusions in patients after coronary artery bypass grafting. Morphological features and a review of possible interventions - S.М. Furkalo (Кардіохірургія та інтервенційна кардіологія)
Within 10 years after coronary artery bypass grafting (CABG) only 60 % of vein grafts and 90 % of the internal mammary artery (IMA) grafts remain patent. Although precise mechanism of atherosclerosis in these patients unknown, several clinical studies reported that atherosclerotic progression occurs more rapidly in grafted arteries than in non-grafted arteries. IMA has a favorable metabolic effect not only in the bypass, but also in the bypassed artery, which is defined by NO products. The occlusion frequency of the initially stenotic artery in the proximal or distal segment was about 22 % after the application of the IMA, and 48 % on average after venous bypass. In multivariate analysis, bypass intervention is independently associated with higher hospital mortality and perioperative complications. If the artery recanalization was successful – mortality was 2.6 %, in the case of a partial success – 5.2 % and in the case of failure, 8.2 % of the patients died. In view of the difficulty of access, spastic reactions, small diameter of the artery and a large area of myocardium that feeds IMA, use of the IMA for the chronic total occlusion (CTO) recanalization is limited. The CTO intervention was performed through the retrograde approach to CTO LAD through IMA and diagonal branch in patient after CABG 10 years ago. We used two microcatheters. The operation was carried out in two stages because of unstable patient condition.